Effects of Walnut Leaf Extract on Seed Germination and Seedling Vigour of Toria (Brassica rapa L. var. toria) - BIRENDRA PRASAD; V.K. SAH; S.K. LAVANΙΑ (Seed Research, 2026)
The significant reduction in seed germination and seedling vigour were observed by the application of walnut leaf extracts in toria (Brassica rapa L. var. toria). However, MGT and T50 as lower values indicated for higher seed vigour, increased with the increased leaf extract concentration, and were lowest in the control. Since the seed germination and seedling vigour were affected negatively by walnut leaf extracts on concentration dependent, therefore, to reduce allelopathic effects on companion toria crop, farmers should remove all fallen walnut leaves.